Influence of organism stimulation with bacterial lipopolysaccharide on nitric oxide production and metabolism in rat heart on the background of metabolic syndrome - O. Ye. Akimov; A. O. Mykytenko; V. O. Kostenko (Сучасні медичні технології)
Aim. The aim of the study was to establish the changes in nitric oxide production and metabolism in rat heart during combined influence of organism stimulation with bacterial lipopolysaccharide (LPS) and modeling of metabolic syndrome (MetS).